Evaluation of bispyribac-sodium for weed control in rainfed rice. - Esqueda-Esquivel, Valentín Alberto; Rosales, Enrique (Agronomía Mesoamericana, 2004)
Two experiments were established in Los Naranjos, Veracruz, México to evaluate the weed control efficacy of the postemergence herbicide bispyribac-sodium, alone and in mixture with other herbicides in rainfed rice and to evaluate the toxicity of bispyribac-sodium to rice. An experiment was established on June 13, 1999, and the second on June 9, 2000 with rice cv Milagro Filipino at 100 kg/ha. A randomized complete block design with eight treatments and the second six with four replication each one was established. In 1999, weed control was evaluated at 15, 30 and 105 days after application (DAA) and in 2000, at 15, 30 and 45 DAA. In both experiments, toxicity was evaluated at 15 and 30 DAA. The main weed species were junglerice [Echinochloa colona (L.) Link.], flatsedge (Cyperus iria L.) and Southern crabgrass [Digitaria ciliaris (Retz.) Koel]. Bispyribacsodium affected only emerged plants; this herbicide efficiently controlled flatsedge at 15 g/ha, junglerice at 22 g/ha and Southern crabgrass was only partially controlled. When bispyribac-sodium was mixed with clomazone or thiobencarb, grass control was increased and a residual herbicide effect was obtained. Bispyribac-sodium was highly selective to rice.